Guest Editorial: Nursing the future: A resource for supporting new graduate nurses’ transition to practice - Corneau, Katherine (Operating Room Nurses Association of Canada Journal, 2025)
Across Canada, newly graduated nurses are entering the workforce during one of the most complex and demanding times in healthcare history. Amid staffing shortages, rising patient acuity, and high workplace expectations, the transition from student to professional nurse can feel overwhelming. Without structured support, new nurses often experience significant stress, self-doubt, and uncertainty in their professional roles. Many leave the profession within the first two years.